FeII4L4 tetrahedron binds and aggregates DNA G-quadruplexes. Issue 43 (25th October 2021) - Zhu, Jinbo; Yan, Zhiqiang; Bošković, Filip; Haynes, Cally J. E.; Kieffer, Marion; Greenfield, Jake L.; Wang, Jin; Nitschke, Jonathan R.; Keyser, Ulrich F.
Abstract : We find FeII4L4 binds to G-quadruplex and forms aggregates. G-quadruplex in the aggregates is protected from digestion by S1 nuclease. Abstract : Since the discovery of the G-quadruplex (G4) structure in telomeres in 1980s, studies have established the role it plays in various biological processes. Here we report binding between DNA G4 and a self-assembled tetrahedral metal-organic cage 1 and consequent formation of aggregates, whereby the cage protects the DNA G4 from cleavage by S1 nuclease. We monitor DNA–cage interaction using fluorescence spectroscopy, firstly by quenching of a fluorescent label appended to the 5′ end of G4. Secondly, we detect the decrease in fluorescence of the G4-selective dyes thioflavin-T and Zn-PPIX bound to various DNA G4 sequences following the addition of cage 1 . Our results demonstrate that 1 interacts with a wide range of G4s. Moreover, gel electrophoresis, circular dichroism and dynamic light scattering measurements establish the binding of 1 to G4 and indicate the formation of aggregate structures. Finally, we find that DNA G4 contained in an aggregate of cage 1 is protected from cleavage by S1 nuclease.